Inversión en I y D en entornos estratégicos: una encuesta de carreras de patentes - Castañeda Sabido, Alejandro (El Colegio de México, A.C., 1994)
This paper surveys the main theoretical contributions that study how firms invest in R&D in a strategic setting. I study the innovation process from the point of view of the supply of new technologies and I review those models that rationalize the innovation process as a stochastic race between firms with the aim of obtaining a patent.